Mitochondrial Fusion Proteins and Human Diseases - Michela Ranieri; Simona Brajkovic; Giulietta Riboldi; Dario Ronchi; Federica Rizzo; Nereo Bresolin; Stefania Corti; Giacomo P. Comi (Neurology Research International, 2013)
Mitochondria are highly dynamic, complex organelles that continuously alter their shape, ranging between two opposite processes, fission and fusion, in response to several stimuli and the metabolic demands of the cell. Alterations in mitochondrial dynamics due to mutations in proteins involved in the fusion-fission machinery represent an important pathogenic mechanism of human diseases. The most relevant proteins involved in the mitochondrial fusion process are three GTPase dynamin-like proteins: mitofusin 1 (MFN1) and 2 (MFN2), located in the outer mitochondrial membrane, and optic atrophy protein 1 (OPA1), in the inner membrane. An expanding number of degenerative disorders are associated with mutations in the genes encoding MFN2 and OPA1, including Charcot-Marie-Tooth disease type 2A and autosomal dominant optic atrophy. While these disorders can still be considered rare, defective mitochondrial dynamics seem to play a significant role in the molecular and cellular pathogenesis of more common neurodegenerative diseases, for example, Alzheimer’s and Parkinson’s diseases. This review provides an overview of the basic molecular mechanisms involved in mitochondrial fusion and focuses on the alteration in mitochondrial DNA amount resulting from impairment of mitochondrial dynamics. We also review the literature describing the main disorders associated with the disruption of mitochondrial fusion.